Cognitive skills explain economic preferences, strategic behavior, and job attachment - Stephen V. Burks; Jeffrey P. Carpenter; Lorenz Götte; Aldo Rustichini (Institute for the Study of Labor (IZA), 2008)
Economic analysis has said little about how an individual's cognitive skills (CS's) are related to the individual's preferences in different choice domains, such as risk-taking or saving, and how preferences in different domains are related to each other. Using a sample of 1,000 trainee truckers we report three findings. First, we show a strong and significant relationship between an individual's cognitive skills and preferences, and between the preferences in different choice domains. The latter relationship may be counterintuitive: a patient individual, more inclined to save, is also more willing to take calculated risks. A second finding is that measures of cognitive skill predict social awareness and choices in a sequential Prisoner's Dilemma game. Subjects with higher CS's more accurately forecast others' behavior, and differentiate their behavior depending on the first mover's choice, returning higher amount for a higher transfer, and lower for a lower one. After controlling for investment motives, subjects with higher CS's also cooperate more as first movers. A third finding concerns on-the-job choices. Our subjects incur a significant financial debt for their training that is forgiven only after twelve months of service. Yet over half leave within the first year, and cognitive skills are also strong predictors of who exits too early, stronger than any other social, economic and personality measure in our data. These results suggest that cognitive skills affect the economic lives of individuals, by systematically changing preferences and choices in a way that favors the economic success of individuals with higher cognitive skills.
urn:nbn:de:101:1-2008072947
Keywords: C81; 330; Field experiment; risk aversion; ambiguity aversion; loss aversion; time preference; Prisoners Dilemma; social dilemma; IQ; MPQ; numeracy; U.S. trucking industry; for-hire carriage; truckload (TL); driver turnover; employment duration; survival model; Kognition; Entscheidung; Präferenztheorie; Gefangenendilemma; Verkehrsberufe; Bildungsertrag; Erwerbsverlauf; Feldforschung; USA